Algebra in the early grades - Kaput, James J. 1942-; Carraher, David William; Blanton, Maria L. (Studies in mathematical thinking and learning, 2008)
Offers a comprehensive, research-based, multi-faceted look at issues in early algebra. This title provides a rationale for a stronger and more sustained approach to algebra in school.